2021
DOI: 10.1177/20406223211041936
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y: a potential theranostic biomarker for diabetic peripheral neuropathy in patients with type-2 diabetes

Abstract: Background: Diabetic peripheral neuropathy (DPN), the most common microvascular complication of type-2 diabetes mellitus (T2DM), results in nontraumatic lower-limb amputations. When DPN is not detected early, disease progression is irreversible. Thus, biomarkers for diagnosing DPN are needed. Methods: We analyzed three data sets of T2DM DPN: two for mouse models (GSE70852 and GSE34889) and one for a human model (GSE24290). We found common differentially expressed genes (DEGs) in the two mouse data sets and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The latest literature has revealed the role of interesting biomarkers, such as the Neuropeptide Y (NPY) and the Elabela Peptide. Cho et al showed that high levels of this marker are visible from the earlier times of diabetic disease, before early symptoms [ 10 ]. Elabela peptide is a product of the renin-angiotensin-aldosterone system; Kaplan et al showed significant growth of this marker in patients with high grades of Rutherford and WIfi scale, with an increase in cardiovascular disease risk [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest literature has revealed the role of interesting biomarkers, such as the Neuropeptide Y (NPY) and the Elabela Peptide. Cho et al showed that high levels of this marker are visible from the earlier times of diabetic disease, before early symptoms [ 10 ]. Elabela peptide is a product of the renin-angiotensin-aldosterone system; Kaplan et al showed significant growth of this marker in patients with high grades of Rutherford and WIfi scale, with an increase in cardiovascular disease risk [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The early identification of DPN and PAD is often challenging and these patients get the correct diagnosis and management when lesions are already irreversible. Thus, screening for early symptoms and signs of DPN and PAD is critical in the clinical practice, to improve patient prognosis and quality of life and reduce healthcare costs [ 10 ]. Despite the possibility to assess the main direct causes of aggressive DFU through different instrumental diagnostic methods, the difficulties related to their execution usually find a late application, when irreversible lesions are already present.…”
Section: Introductionmentioning
confidence: 99%
“…2 It is reported that approximately 50% of patients with T2DM would be accompanied by diabetic peripheral neuropathy (DPN), one of the most frequent chronic complications of diabetes mellitus. 3,4 DPN is characterized by neuropathic pain, numbness, and sensory abnormality on symmetrical, bilateral distal limbs, which not only increases the risks of foot ulceration and even lower-limb amputation but also results in a substantial effect on the patient's health and a heavy financial burden. 5 Up to now, the potential pathogenic mechanisms of DPN have not yet been completely elucidated, which limits the further exploration of useful prevention and treatment strategies for DPN.…”
Section: Introductionmentioning
confidence: 99%